Depotentiation from Potentiated Synaptic Strength in a Tristable System of Coupled Phosphatase and Kinase - Chen, Mengjiao; Ren, Wei; Wang, Xingang (Frontiers in Computational Neuroscience, 2016)
Long-term potentiation (LTP) of synaptic strength is strongly implicated in learning and memory. On the other hand, depotentiation, the reversal of synaptic strength from potentiated LTP state to the pre-LTP level, is required in extinction of the obsolete memory. A generic tristable system, which couples the phosphatase and kinase switches, exclusively explains how moderate and high elevation of intracellular calcium concentration triggers long-term depression (LTD) and LTP, respectively. The present study, introducing calcium influx and calcium release from internal store into the tristable system, further show that significant elevation of cytoplasmic calcium concentration switches activation of both kinase and phosphatase to their basal states, thereby depotentiate the synaptic strength. A phase-plane analysis of the combined model was employed to explain the previously reported depotentiation in experiments and predict a threshold-like effect with calcium concentration. The results not only reveal a mechanism of NMDAR- and mGluR-dependent depotentiation, but also predict further experiments about the role of internal calcium store in induction of depotentiation and extinction of established memories.